ANALYSIS OF QUALITY OF WORKLIFE (QWL) IMPLEMENTATION AGAINST JOB SATISFACTION AND COMMITMENT OF THE EMPLOYEES. - Indah Kusuma Hayati (The Management Journal of Binaniaga, 2016)
Abstract. Increased productivity needs being in line with the increase in employee performance. To be able to improve employee performance, companies must create working conditions that offer incentives for employees to satisfy them with the system running in the company(????). The purpose application of Quality of Work Life (QWL) in an enterprise is to improve employee satisfaction on the job(???). Employee job satisfaction is one important aspect to consider in efforts to improve the human resources quality of an enterprise. Employees who have high job satisfaction, will generally have a high commitment to the company. High employee commitment will give beneficial contribution to the company to increase productivity of both employees and companies. This study aims to analyze the effect of the QWL application on job satisfaction and employee commitment as well as analyzing the effect of job satisfaction on employee commitment. The study is conducted by giving questionnaire to 120 employees SBU (Strategic Business Unit) 1 PT. PGN, which is present in three areas, namely Hosbun, Bogor and Jakarta East. Hypothesis testing method using the model Structural Equation Model (SEM) with PLS.The results of the analysis indicate that the application of QWL hypothesis has no effect on job satisfaction of employees. Application of QWL and job satisfaction significantly influence employee commitment. The better implementation of QWL and the higher levels of job satisfaction will increase employee commitment to the company.Keywords : Quality of work life, job satisfaction and employee commitment, SEM PLS